'Less is more': validation with Rasch analysis of five short-forms for the Brain Injury Rehabilitation Trust Personality Questionnaires (BIRT-PQs). (5th December 2020) - Pellicciari, Leonardo; Piscitelli, Daniele; Basagni, Benedetta; De Tanti, Antonio; Algeri, Lorella; Caselli, Serena; Ciurli, Maria Paola; Conforti, Jessica; Estraneo, Anna; Moretta, Pasquale; Gambini, Maria Grazia; Inzaghi, Maria Grazia; et al.
ABSTRACT: Background: Previous analyses demonstrated a lack of unidimensionality, item redundancy, and substantial administrative burden for the Brain Injury Rehabilitation Trust Personality Questionnaires (BIRT-PQs). Objective: To use Rasch Analysis to calibrate five short-forms of the BIRT-PQs, satisfying the Rasch model requirements. Methods: BIRT-PQs data from 154 patients with severe Acquired Brain Injury (s-ABI) and their caregivers (total sample = 308) underwent Rasch analysis to examine their internal construct validity and reliability according to the Rasch model. Results: The base Rasch analyses did not show sufficient internal construct validity according to the Rasch model for all five BIRT-PQs. After rescoring 18 items, and deleting 75 of 150 items, adequate internal construct validity was achieved for all five BIRT-PQs short forms (model chi-square p -values ranging from 0.0053 to 0.6675), with reliability values compatible with individual measurements. Conclusions: After extensive modifications, including a 48% reduction of the item load, we obtained five short forms of the BIRT-PQs satisfying the strict measurement requirements of the Rasch model. The ordinal-to-interval measurement conversion tables allow measuring on the same metric the perception of the neurobehavioral disability for both patients with s-ABI and their caregivers.